2016
DOI: 10.1007/s10815-016-0779-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing of blastocyst rate and gene expression in co-culture of bovine embryos with adult adipose tissue-derived mesenchymal stem cells

Abstract: Purpose Despite advances in the composition of defined embryo culture media, co-culture with somatic cells is still used for bovine in vitro embryo production (IVEP) in many laboratories worldwide. Granulosa cells are most often used for this purpose, although recent work suggests that co-culture with stem cells of adult or embryonic origin or their derived biomaterials may improve mouse, cattle, and pig embryo development. Materials and methods In experiment 1, in vitro produced bovine embryos were co-culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
2
13
2
Order By: Relevance
“…In reproductive fluids, Almiñana et al showed that mRNAs encoding ribosomal proteins of the large (RPL) and small subunit (RPS) were the most abundant protein-coding RNAs within oviductal EVs ( 34 ). These results are in line with studies in EVs from other body fluids including saliva ( 58 ) and urine ( 59 ) It is possible that the numerous ribosomal proteins identified in our ffEV preparations, and those identified by others, may form RNA–ribonucleoprotein complexes that function to package RNAs into EVs and, thus, participate in RNA maintenance ( 57 ) or RNA degradation in exosomes. The presence of numerous RBPs and ribosomal proteins in ffEVs may suggest a possible role for the proteins in RNA sorting, which was also reported in EVs of different origins ( 60 ).…”
Section: Discussionsupporting
confidence: 90%
“…In reproductive fluids, Almiñana et al showed that mRNAs encoding ribosomal proteins of the large (RPL) and small subunit (RPS) were the most abundant protein-coding RNAs within oviductal EVs ( 34 ). These results are in line with studies in EVs from other body fluids including saliva ( 58 ) and urine ( 59 ) It is possible that the numerous ribosomal proteins identified in our ffEV preparations, and those identified by others, may form RNA–ribonucleoprotein complexes that function to package RNAs into EVs and, thus, participate in RNA maintenance ( 57 ) or RNA degradation in exosomes. The presence of numerous RBPs and ribosomal proteins in ffEVs may suggest a possible role for the proteins in RNA sorting, which was also reported in EVs of different origins ( 60 ).…”
Section: Discussionsupporting
confidence: 90%
“…Of the cell passages examined in this study, passage 5 seemed to be the most efficient in the performance of nuclear transfer due to its high level of stemness, multipotency, and the low level of chromatin compaction [76]. The embryo production rate was also shown to improve when embryos were co-cultured with MSC [77], representing in yet another way the importance of MSC in addressing commercial goals.…”
Section: Bovine Mesenchymal Stem Cell Therapymentioning
confidence: 99%
“…The higher cell concentration (10 4 cells/ml) may be more favorable than lower (10 3 cells/ml) cell concentration and conditioned medium, though blastocyst rates may be more (Miranda et al, 2016).…”
Section: Reproductive Systemmentioning
confidence: 99%
“…In vitro fertilized embryos on culturing with bAD‐MSCs (10 3 /10 4 cells/ml) may show better blastocyst rates and quality as determined by POU5F1 and G6PDH. The higher cell concentration (10 4 cells/ml) may be more favorable than lower (10 3 cells/ml) cell concentration and conditioned medium, though blastocyst rates may be more (Miranda et al, ).…”
Section: Potential Applicationsmentioning
confidence: 99%